Robust optimization using Bayesian optimization algorithm: Early detection of non-robust solutions - Kaedi, Marjan; Ahn, Chang Wook (Applied soft computing, 2017)
[Display omitted] •We focus on Bayesian optimization algorithm (BOA) for robust optimization.•We adopt BOA for speeding up the probabilistic robustness evaluation.•The Bayesian networks are used to identify the non-robust solutions.•The non-robust solutions are detected and evaluation of their fitness is omitted.•Our method reduces the number of fitness evaluations and improves the robustness. Probabilistic robustness evaluation is a promising approach to evolutionary robust optimization; however, high computational time arises. In this paper, we apply this approach to the Bayesian optimization algorithm (BOA) with a view to improving its computational time. To this end, we analyze the Bayesian networks constructed in BOA in order to extract the patterns of non-robust solutions. In each generation, the solutions that match the extracted patterns are detected and then discarded from the process of evaluation; therefore, the computational time in discovering the robust solutions decreases. The experimental results demonstrate that our proposed method reduces computational time, while increasing the robustness of solutions.